Nonlinear Stability of the Bipolar Navier-Stokes-Poisson System with Boundary - Tiantian Yu; Yong Li (Advances in Mathematical Physics)
The combined quasineutral and zero-viscosity limits of the bipolar Navier-Stokes-Poisson system with boundary are rigorously proved by establishing the nonlinear stability of the approximate solutions. Based on the conormal energy estimates, we showed that the solutions for the original system converge strongly in H3 space towards the solutions of the one-fluid compressible Euler system as long as the amplitude of the boundary layers is small enough.